The Influence of Online Learning Communication Toward Students Achievement : Pengaruh Komunikasi Pembelajaran Daring Terhadap Capaian Hasil Belajar Siswa - Muzakki, Achmad; Rochmaniah, Ainur (Indonesian Journal of Innovation Studies, 2023)
The covid19 pandemic has forced the world of education, especially in terms of learning, to adapt a little to new methods, namely learning boldly or online. Learning boldly can be done at home with the help of apps like zoom, or google meet. In practice, courageous learning communication that is often encountered encounters many obstacles such as the internet network, the material presented and others. Many problems that occur in learning with the bold method (online) for students and teaching staff are the basis for this research to be written. The method used in this research is quantitative, using total sampling for sampling and distributing questionnaires in collecting data. The sample in this study was 50 students at LBB Lentera Cendekia. The result of this research is that there is an influence of learning communication which has a positive influence on the achievement of student learning outcomes. This is evidenced by the R value which is 0.666 and the courageous learning at LBB Lentera Cendekia is equal to zero, meaning that it does not affect the achievement of student learning outcomes.